PENGATURAN SUHU UNTUK MENGATASI BAYI TERBAKAR BERBASIS ARDUINO DAN LABVIEW PADA INFANT INCUBATOR - Ramdani, Dicky Rivaldo; Nugroho, Andi Kurniawan; Destyningtias, Budiani (Elektrika, 2019)
An incubator is a place designed to maintain a certain temperature condition. Incubators are often found in hospitals and farms. In hospitals, the Incubator functions to warm newborns, or premature babies. On farms, this incubator is usually used for egg hatchers and as a place for newly hatched chicks. Incubators are usually in the form of a room or box (box) of a certain size. In this research will be designed a prototype to modify the infant incubator by adding sensors to regulate the temperature and control using a Arduino microcontroller. This incubator has a measurement system and temperature regulation using LM35 sensors, heaters and fans as actuators that can cool the incubator room with Arduino as controlling. Temperature setting will be monitored by LABVIEW. In the Arduino system a program can be set up that can adjust the temperature . The temperature required by the premature baby, so that it can maintain the stability of the temperature. If the temperature in the incubator is smaller than the temperature setting, the heater will turn on and the fan speed will decrease to increase the temperature according to the settings entered. If the temperature in the incubator is greater than the temperature setting entered, the heater will turn off. The results showed that the linear regression value between the temperature values with the ADC value of y = 0.4883x with a determination coefficient of 1, while the linear regression value between the temperature with a voltage value of y = 99.481x with a coefficient of 0.9984.Keywords: Infant Incubator, temperature sensor, LM35.